Pengaruh Pengawasan Orang Tua terhadap Kualitas Belajar Peserta Didik dalam Sistem Pembelajaran Jarak Jauh - Ratna Azizah Andi (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2021)
The purpose of this discussion is to find out whether parental supervision influences the quality of student learning in the distance learning period. Since the outbreak of the COVID-19 pandemic in mid-March 2020, all physical learning activities at schools have stopped. The central and regional governments swiftly issue online learning policies or commonly referred to as distance learning (PJJ). The various obstacles faced in this PJJ certainly affect the quality of student learning. In addition to the various problems faced, a large role for parental supervision is also needed in distance learning because teachers as facilitators at school cannot fully supervise student’s activities. Parental involvement has a positive impact on student achievement, such as higher test scores and graduation rates, as well as the influence on student development indicators, including better behavior and social skills, strong belief in the importance of education, and so on. The role of parents at home is to accompany children in doing school assignments, limit permits for activities outside the home, coordinate with teachers and schools, and also help students implement a clean and healthy lifestyle